DISASTER PREPAREDNESS AT PUBLIC HEALTH CENTER (PHC) BY SCORING ANALYSIS OF GENERAL ASPECTS, HEALTH CARE, SURVEILLANCE, ENVIRONMENTAL SANITATION AND LOGISTICS - Irma Prasetyowati; Yennike Tri Herawati; Pudjo Wahjudi (UNEJ e-Proceeding)
Preparedness according to the Constitution ofIndonesia No. 24 2007 on Disaster Management is aseries of activities done in order to anticipatedisasters through the organization as well as throughappropriate and useful activities. The disastermanagement in Indonesia adopts the paradigm ofrisk reduction, disaster management which aims toimprove the ability of communities to manage andreduce the risk of disaster to society the disastersubjects. This prevention is focused on pre-disasterphase to minimize the risks (BNPB, 2009). Jember islocated at the altitude 0-3330 meters above the sealevel. Its area with the altitude of 100-500 metersabove the sea level is the largest area, 1240.77 km²or 37.68% of total area of Jember. Meanwhile, thenarrowest area is the area with a height of over2,000 meters above the sea level with 31, 34 km² or0.95% of the area of Jember. Jember has atopographic character of fertile plains canyon in theCentral and South parts and is surrounded bymountains that extends to the boarder of East andWest. The area of South West has a plateau with aheight of 0-25 meters above the sea level, while theNortheast area, which borders with Bondowoso, andthe Southeast area bordering Banyuwangi has over1,000 meters above the sea level (PPSP 2012).Based on the geographical conditions, the potentialdisasters that may occur are such as, floods,landslides and tsunami. The potential disaster isinfluenced by Jember topography consisting ofplains, mountains, and beaches. The data fromJember Health Department in 2011 showed thatthere were 21 of 31 Districts potentially disaster mayhappen.When the disaster happens, it causes humancasualties and property losses. The human casualtiescause insecurity to the health status of affectedpeople and communities living around the disasterarea. Therefore, the acceleration of the handling ofthe victim is not only necessary in emergencyresponse, but also it should be emphasized on theprepared efforts carried out as early as possible, sothat the number of casualties can be minimized.Preparedness is a shared responsibility ofstakeholders, central government, localgovernments, communities and the business world.The role has been written in constitution No. 242007 about Disaster Management.One of the responsible stakeholders in implementingpreparedness activities is Public Health Center (PHC).PHC functions as the central driver of health insight,family and community empowerment center, andthe first level health care center which is qualifiedand affordable. Especially, on the third function, itincludes aspects of public health and personal healthservices including handling the emergency patient inthe community. (Community Health, Department ofHealth, 2005).